CRYPTOCURRENCIES ARE THE MONEY OF THE DIGITAL ECONOMY (Academia Science Repository, 2023)
In the article, actual problems of the current state and prospects for the use of cryptocurrencies in Russia and abroad are considered. The problems faced by foreign countries when using cryptocurrencies are identified. An analysis of the current state and prospects for the development of the Russian payment system allowed the author to identify the risks of introducing restrictions on cash payments, and payments using electronic money, including cryptocurrencies, and to give specific recommendations for improving Russia's monetary policy in the new conditions.